El año de Gracia and the Displacement of the Word - Catherine G. Bellver (Studies in 20th & 21st Century Literature, 1992)
The power of the established, self-sufficient written word is considerable. Written texts not only furnish material, incentive, or direction for new texts, they also inspire, orient, and mold those who read them. El año de Gracia, a novel by Cristina Fernández Cubas (1985), vividly illustrates the imprint novels can leave on a young mind. The protagonist learns, however, that the concept of the world he formed on the basis of literary models is erroneous. In El año de Gracia literature fails to sustain meaning, and meaning itself becomes irrelevant. Both oral and written discourse are in some way restricted, displaced, and subverted. The voice is deprived of its potential to tell stories by the linguistic impasse between the protagonist and his companion; only the magical, non-discursive dimension of the spoken word affords a tenuous conduit for interchange between the two. Writing, for its part, cannot also flourish because the addresser cannot find an accommodating addressee for his text. Daniel must forfeit his desire for an ideal reader in favor of the private pleasure of writing as a process. He discovers that scientists and ecologists are not any better disposed to communication than the coarse shepherd Grock. Betrayed by both literature and society, the protagonist turns away from both. As writer he learns that only the act of narration is meaningful, not literary models. Yet since his oral and written words are displaced, communication on a collective level ceases.
Keywords: text; El año de Gracia; Cristina Fernández Cubas; meaning; discourse; voice; reader/ writer relationship; narration; communication; collective communication; Spanish narrative